A proposal for the addressing the needs of the pediatric pulmonary work force. Issue 8 (12th June 2020) - Gaston, Benjamin; Laguna, Theresa A.; Noah, Terry L.; Hagood, James; Voynow, Judith; Ferkol, Thomas; Hershenson, Marc; Boyne, Katie; Delecaris, Angela; Ross, Kristie; Gozal, David; Celedón, Juan C.; et al.
Abstract: Unprecedented opportunities and daunting difficulties are anticipated in the future of pediatric pulmonary medicine. To address these issues and optimize pediatric pulmonary training, a group of faculty from various institutions met in 2019 and proposed specific, long‐term solutions to the emerging problems in the field. Input on these ideas was then solicited more broadly from faculty with relevant expertise and from recent trainees. This proposal is a synthesis of these ideas. Pediatric pulmonology was among the first pediatric specialties to be grounded deliberately in science, requiring its fellows to demonstrate expertise in scientific inquiry (1). In the future, we will need more training in science, not less. Specifically, the scope of scientific inquiry will need to be broader. The proposal outlined below is designed to help optimize the practices of current providers and to prepare the next generation to be leaders in pediatric care in the future. We are optimistic that this can be accomplished. Our broad objectives are (a) to meet the pediatric subspecialty workforce demand by increasing interest and participation in pediatric pulmonary training; (b) to modernize training to ensure that future pediatric pulmonologists will be prepared clinically and scientifically for the future of the field; (c) to train pediatric pulmonologists who will add value in the future of pediatric healthcare, complemented by advanced practice providers and artificial intelligence systems that are well‐informed to optimize quality healthcare delivery; and (d) to decrease the cost and improve the quality of care provided to children with respiratory diseases.